(x + y)2 = (x-4)
(x + y) {}^{2}  - (x - y) {}^{2}
factorise ​

Question

(x + y)2 = (x-4)
(x + y) {}^{2}  - (x - y) {}^{2}
factorise ​

in progress 0
Ariana 4 months 2021-08-01T09:36:26+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-01T09:38:15+00:00

    Answer:

    x=−2y−4

    Step-by-step explanation

    (x+y)(2)=x−4

    2x+2y+−x=x−4+−x

    x+2y=−4

    x+2y+−2y=−4+−2y

    x=−2y−4

    i hope this is correct and that this helps answers your question.

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )